Persentase Post Larva Udang Galah (Macrobrachium rosenbergii) Dengan Pemberian L-Ascorbyl-2-Monophosphate-Magnesium Dalam Air - Raden Roro Sri Pudji Sinarni Dewi; Bambang Iswanto (Jurnal Perikanan Universitas Gadjah Mada, 2007)
The aim of this study was to improve the production homogeneity of freshwater prawn post larva by the addition of L-ascorbyl-2-monophosphate-Mg (AMP-Mg) in the water during rearing period. AMP-Mg was given to the water every three days with different concentrations of 0; 0.5; 1.0; and 1.5 mg/l. The density of larvae was 50 larvae/l. Larvae were fed Artemia and egg custard during rearing period. The results showed that AMP-Mg did not significantly influence larval metamorphose rate, post larvae percentage, and survival rate of prawn. However, AMP-Mg addition could improve homogeneity of post larvae production. The optimum AMP-Mg concentration was 0.5 mg/l.